2021
DOI: 10.1007/s10620-021-07273-y
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine with Allopurinol Is a Promising First-Line Therapy for Inflammatory Bowel Diseases

Abstract: Background Beneficial response to first-line immunosuppressive azathioprine in patients with inflammatory bowel disease (IBD) is low due to high rates of adverse events. Co-administrating allopurinol has been shown to improve tolerability. However, data on this co-therapy as first-line treatment are scarce. Aim Retrospective comparison of long-term effectiveness and safety of first-line low-dose azathioprine-allopurinol co-therapy (LDAA) with first-line azathioprine mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…This recommendation is in line with newly published retrospective data from the UK in a large single center population of IBD patients. 30 We do not recommend this approach if TPMT has not been measured because no data exist as to whether it could lead to unexpected AE in patients with a heterozygote TPMT genotype. When combination therapy is given, the dose of AZA should be 50 mg for patients weighing between 50 and 100 kg and 75 mg for patients over 100 kg, in combination with 100 mg allopurinol.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is in line with newly published retrospective data from the UK in a large single center population of IBD patients. 30 We do not recommend this approach if TPMT has not been measured because no data exist as to whether it could lead to unexpected AE in patients with a heterozygote TPMT genotype. When combination therapy is given, the dose of AZA should be 50 mg for patients weighing between 50 and 100 kg and 75 mg for patients over 100 kg, in combination with 100 mg allopurinol.…”
Section: Discussionmentioning
confidence: 99%
“…This combination has also been tested in thiopurine‐naïve patients in RCTs and retrospective cohort studies, and though heterogeneous, the evidence suggests higher rates of clinical remission in the combination versus azathioprine alone group. 28 , 29 , 30 Although allopurinol–azathioprine combination is an option in shunters, it may also be used at centers where TDM is unavailable. Splitting the dose of azathioprine has also been suggested to overcome thiopurine resistance by reducing 6‐MMP levels via suboptimal substrate affinity for TMPT (and hence reduced TPMT activity) due to reduced dose in each administration.…”
Section: Genetic Polymorphisms Impacting Thiopurine Metabolismmentioning
confidence: 99%
“…Low‐dose azathioprine along with allopurinol is one such measure (allopurinol is a xanthine oxidase inhibitor that “deshunts” the metabolism towards the HPRT pathway, and metabolites such as thioxanthine inhibit TPMT) that the authors used in shunters and achieved therapeutic 6‐TG levels in ~40% patients. This combination has also been tested in thiopurine‐naïve patients in RCTs and retrospective cohort studies, and though heterogeneous, the evidence suggests higher rates of clinical remission in the combination versus azathioprine alone group 28–30 . Although allopurinol–azathioprine combination is an option in shunters, it may also be used at centers where TDM is unavailable.…”
Section: Genetic Polymorphisms Impacting Thiopurine Metabolismmentioning
confidence: 99%
“…With respect to retrospective studies, there are numerous groups that have published about the efficacy and safety of combination azathioprine and allopurinol use. All these groups demonstrated that combination azathioprine and allopurinol was useful, safe and effective in the management of IBD [76][77][78][79][80][81]. These studies reported a lower level of cessation for the combination therapy groups when compared to the azathioprine monotherapy groups as well as improved efficacy over monotherapy alone.…”
Section: Trials Examining the Use Of Azathioprine And Allopurinol In Ibdmentioning
confidence: 95%
“…The dosage of allopurinol used in these studies varied between 100 and 300 mg with 100 mg being the most common dose used. Some groups demonstrated that patients who experienced LFT derangement even after the switch from azathioprine monotherapy to combination azathioprine and allopurinol could have their LFT derangement normalised with an increased dose of allopurinol, from 100 mg to 200-300 mg daily, in almost all cases [76,79,81].…”
Section: Trials Examining the Use Of Azathioprine And Allopurinol In Ibdmentioning
confidence: 99%